2xy + y + 4x = 36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(4x2+2xy+y2)(2x-y)-(2x-y)(4x2-2xy+y2)
=(2x3-y3)-(2x+y)(4x2-2xy+y2)
=(2x3-y3)-(2x3+y3)
=2x3-y3-2x3+y3
=0
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
( 2x + y ) ( 4x2 - 2xy + y2 ) - ( 2x - y ) ( 4x2 + 2xy + y2 )
= 8x3 + y3 - ( 8x3 - y3 )
= 2y3
\(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(=8x^3+y^3-\left(8x^3-y^3\right)\)
\(=8x^3+y^3-8x^3+y^3\)
\(=\left(8x^3-8x^3\right)+\left(y^3+y^3\right)\)
\(=2y^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Sửa đề \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(=8x^3+y^3-8x^3+y^3=2y^3\)
\(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(=8x^3+y^3-8x^3+y^3\)
\(=2y^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)x2-25+y2+2xy
=(x2+2xy+y2)-25
=(x+y)2-52
=(x+y+5)(x+y-5)
b)x3+9x2-4x-36
=(x3+9x2)-(4x+36)
=x2(x+9)-4(x+9)
=(x2-4)(x+9)
=(x+2)(x-2)(x+9)
Đúng thì tick cho mình nhé !
a,\(x^2-25+y^2+2xy=\left(x^2+2xy+y^2\right)-25\)
\(=\left(x+y\right)^2-25\)
\(=\left(x+y\right)^2-5^2\)
\(=\left(x+y-5\right)\left(x+y+5\right)\)
b,\(x^3+9x^2-4x-36=\left(x^3+9x^2\right)-\left(4x+36\right)\)
\(=x^2\left(x+9\right)-4\left(x+9\right)\)
\(=\left(x^2-4\right)\left(x+9\right)\)
\(=\left(x^2-2^2\right)\left(x+9\right)\)
\(=\left(x+2\right)\left(x-2\right)\left(x+9\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-2xy+y^2-xz+yz\)
= \(\left(x-y\right)^2-z\left(x-y\right)\)
= \(\left(x-y\right)\left(x-y-z\right)\)
b) \(x^3+9x^2-4x-36\)
= \(x^3-2x^2+11x^2-22x+18x-36\)
= \(x^2\left(x-2\right)+11x\left(x-2\right)+18\left(x-2\right)\)
= \(\left(x-2\right)\left(x^2+11x+18\right)\)
= \(\left(x-2\right)\left(x^2+2x+9x+18\right)\)
= \(\left(x-2\right)\left(x+2\right)\left(x+9\right)\)
Chuc ban hoc tot
![](https://rs.olm.vn/images/avt/0.png?1311)
f) = x2( x - 4 ) - 9( x - 4 ) = ( x - 4 )( x - 3 )( x + 3 )
g) = 4( x - y ) + ( x - y )2 = ( x - y )( x - y + 4 )
h) = x3( x + 1 ) + ( x - 1 )( x + 1 ) = ( x + 1 )( x3 + x - 1 )
i) = ( x - y )( x + y ) - 4( x + y ) = ( x + y )( x - y - 4 )
j) = ( x - y )( x2 + xy + y2 ) - 3( x - y ) = ( x - y )( x2 + xy + y2 - 3 )
Trả lời:
f, x3 - 4x2 - 9x + 36 = ( x3 - 4x2 ) - ( 9x - 36 ) = x2 ( x - 4 ) - 9 ( x - 4 ) = ( x - 4 )( x2 - 9 ) = ( x - 4 )( x - 3 )( x + 3 )
g, 4x - 4y + x2 - 2xy + y2 = ( 4x - 4y ) + ( x2 - 2xy + y2 ) = 4 ( x - y ) + ( x - y )2 = ( x - y ) ( 4 + x - y )
h, x4 + x3 + x2 - 1 = ( x4 + x3 ) + ( x2 - 1 ) = x3 ( x + 1 ) + ( x - 1 )( x + 1 ) = ( x + 1 )( x3 + x - 1 )
i, x2 - y2 - 4x - 4y = ( x2 - y2 ) - ( 4x + 4y ) = ( x - y )( x + y ) - 4 ( x + y ) = ( x + y )( x - y - 4 )
j, x3 - y3 - 3x + 3y = ( x3 - y3 ) - ( 3x - 3y ) = ( x - y )( x2 + xy + y2 ) - 3 ( x - y ) = ( x - y )( x2 + xy + y2 - 3 )
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(\left(y+3\right)\left(y^2-3y+9\right)-\left(60-y^3\right)\)
\(=y^3+27-60+y^3\)
\(=2y^3-33\)
b) Ta có: \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(=8x^3+y^3-8x^3+y^3\)
\(=2y^3\)
![](https://rs.olm.vn/images/avt/0.png?1311)